Efeito do ultrassom e plasma a frio nas propriedades do suco de acerola - Oliveira, Valéria Santos de (2017)
Recently, new technologies have been developed by the food industry in order to achieve safe processing and focusing on maintaining their nutritional properties. In this manner, the objective of this work was to study the influence of an ultrasonic process on the physical (pH, ºBrix, color, cloud value), chemical (phenolic compounds, DPPH antioxidant capacity, FRAP and ABTS, hydrogen peroxide, complex vitamins B, vitamin C, vitamins A and E, pro vitamin D, lycopene and carotenoids) and biochemical (POD and PAX enzymes) properties of acerola juice and prebiotic acerola juice submitted to ultrasonic treatment under temperatures of 10, 23 and 40ºC, in powers of 500, 1500 e 2500 W/L and in times varying from 2.5 to 15 minutes. Regarding the treatment with cold plasma, it was assessed physical and chemical aspects in acerola juice and prebiotic acerola juice, under fluxes ranging from 10, 15 and 20 mL of N2/min, and maximum power of 80 kV in periods of 10, 15 and 20 minutes. At the end of the processing, the best parameters presented for the acerola juice studied were the cloud value, the antioxidant capacity of the three methods studied (DPPH, ABTS and FRAP), enzymatic activity, vitamin C and total carotenoids. The concentration of hydrogen peroxide presented increased throughout the experiment, already expected in ultrasonic treatment. Despite the degradation of vitamins B3 and B5 in the sonicated acerola juice, the addition of frutoligosaccharide protected the juice matrix and increased the concentration of the vitamins B at the end of the experiment. Summarizing, the ultrasonic treatment for acerola juice was well tolerated for the parameters presented, mainly by the increasing the ascorbic acid concentration and total antioxidant capacity throughout the experiment. The results for the cold plasma processing were very satisfactory. Virtually all parameters studied increased after processing, with the exception of phenolic compounds and antioxidant capacity. However, the addition of the frutoligosaccharide acted as a protective agent and prevented losses during processing. Another interesting observation in the treatment with cold plasma was the decrease of the amount of hydrogen peroxide concentration, thus avoiding future nutritional losses of this juice.